Entre el poder local y el Estado: las Juntas de Hacienda en el Ecuador del siglo XIX - Velasco Herrera, Viviana (Revista de historia., 2014)
The article explores the complex forms of administration of the Public Treasury in the Ecuadorian process of state building. To this end the analysis is centered in the Juntas de Hacienda, bodies of Colonial origin that had several functions, among which we can count: the redistribution of Public Treasury resources –especially those linked to the upkeep of military forces and the most necessary public works- and the validation of the collections employees. With that background, the article shows how the Juntas de Hacienda was spaces of negotiation of resources among the local and state powers.